Effect of Selenium Biofortification and Beneficial Microorganism Inoculation on Yield, Quality and Antioxidant Properties of Shallot Bulbs - Golubkina, Nadezhda (Plants (Basel), 2019)
Plant biofortification with selenium in interaction with the application of an arbuscular mycorrhizal fungi (AMF)-based formulate, with the goal of enhancing Se bioavailability, is beneficial for the development of the environmentally friendly production of functional food with a high content of this microelement. Research was carried out in order to assess the effects of an AMF-based formulate and a non-inoculated control in factorial combination with two selenium treatments with an organic (selenocystine) or inorganic form (sodium selenate) and a non-treated control on the yield, quality, antioxidant properties, and elemental composition of shallot (Allium cepa L. Aggregatum group). Selenocystine showed the best effect on the growth and yield of mycorrhized plants, whereas sodium selenate was the most effective on the non-inoculated plants. The soluble solids, total sugars, monosaccharides, titratable acidity, and proteins attained higher values upon AMF inoculation. Sodium selenate resulted in higher soluble solids, total sugars and monosaccharide content, and titratable acidity than the non-treated control, and it also resulted in higher monosaccharides when compared to selenocystine; the latter showed higher protein content than the control. Calcium, Na, S, and Cl bulb concentrations were higher in the plants inoculated with the beneficial microorganisms. Calcium and sodium concentrations were higher in the bulbs of plants treated with both the selenium forms than in the control. Selenocystine-treated plants showed enhanced accumulation of sulfur and chlorine compared to the untreated plants. The AMF inoculation increased the bulb selenium content by 530%, and the Se biofortification with selenocystine and sodium selenate increased this value by 36% and 21%, respectively, compared to control plants. The AMF-based formulate led to increases in ascorbic acid and antioxidant activity when compared to the non-inoculated control. The bulb ascorbic acid was increased by fortification with both selenium forms when compared to the non-treated control. The results of our investigation showed that both AMF and selenium application represent environmentally friendly strategies to enhance the overall yield and quality performances of shallot bulbs, as well as their selenium content.